A study on the strength development of geopolymer concrete using fly ash - Chokkalingam, Ramesh Babu; N, Ganesan (International Journal of Engineering and Technology, 2017)
Cement consumption is increasing day by day due to the tremendous development in the infrastructure facilities. The production of one ton of cement emits approximately one ton of carbon dioxide to the atmosphere. In order to reduce the use of cement a new-generation concrete has been developed such as geopolymer concrete (GPC).Geopolymer Geopolymer is a new material which has the potential to replace ordinary Portland cement. It is an inorganic material synthesized by alkali activation of amorphous aluminosilicates at ambient or slightly increased temperatures having an amorphous to semi-crystalline polymeric structure. In this study, low calcium flyash from Tuticorin was used to produce geopolymer concrete. The geopolymer was synthesized with sodium silicate and sodium hydroxide solutions. The sodium hydroxide pellets was dissolved in the distilled water to make free from mixing water contaminants. The ratio of sodium silicate and sodium hydroxide ratio was kept as 2.5. The concentration of sodium hydroxide solution is 12 Molarity (12M). Other materials used are locally available coarse aggregate and fine sand in surface dry condition. A polycarboxlate HRWRA La Hypercrete S25was used. Cubes of size 100mm were cast for six mix proportions of 450kg/m3 flyash+0.35W/B, 500 kg/m3 flyash+0.35W/B, 550kg/m3 flyash+0.35W/B, 450kg/m3 flyash+.0.40 W/B, 500kg/m3 fly ash+0.40W/B and 550kg/m3 flyash+0.40W/B. The specimens after casting in moulds were kept in oven at 60Â°C for 6 hours and left to air dry at room temperature and tested at 7 and 28 days. The test results revealed the compressive strength of 30 Mpa was achieved. There was not much significant difference in strength development at 28 days between the mixes due to the increase of flyash content. The microstructural images at 28 days revealed that there was not much difference in the microstructure due to the variation in flyash content from 450 kg/m3 to 550 kg/m3.